Mitigating cardiac allograft vasculopathy in a murine model via CD40-TRAF6 blockade and cyclosporin A synergy - Yajun Huang; Junlin Lai; Xing Chen; Jinfeng Yang; Chenghao Li; Yixuan Wang; Yuqi Chen; Tian Xia; Yijie Luo; Wai Yen Yim; Xiangchao Ding; Guohua Wang (Scientific Reports)
Abstract The interactions between CD40 and tumor necrosis factor receptor-associated factor 6 (TRAF6) are implicated in chronic inflammation and fibrosis. Given their poorly understood role in chronic transplant rejection, our study focused on investigating the CD40-TRAF6 interactions in murine models of cardiac transplantation, particularly in relation to cardiac allograft vasculopathy (CAV). We established murine heart transplantation models using BALB/C to C57BL/6 and H-2bm12 to C57BL/6 pairings. A specific antagonist for TRAF6 was administered post-transplantation, either alone or in combination with cyclosporin A (CsA). We analyzed cells infiltrating the cardiac allografts and splenic immune cells. Additionally, We explore the potential mechanistic effects of TRAF6 inhibition in CAV by bone marrow-derived macrophages (BMDMs) co-culture. The inhibition of CD40-TRAF6 interaction significantly prolonged the survival of cardiac allografts. When combined with CsA, this treatment induced long-term survival of the allografts. Specifically, in the H-2bm12 to C57BL/6 heart transplantation model, inhibiting TRAF6 mitigated the development of CAV. This blockade led to a decrease in CD11b + and CD4 + cells within the allografts. In vitro experiments showed that TRAF6 inhibition had limited effects on mixed lymphocyte culture responses and minimally affected the proliferation of naive CD4 + cells activated by CD3/CD28. Furthermore, BMDMs under CD40-TRAF6 inhibition were more likely to differentiate into an anti-inflammatory phenotype, and their migration capability was reduced. Our findings demonstrate that inhibiting the TRAF6 pathway can significantly ameliorate both acute and chronic allograft rejection. The combination with CsA appears to have a synergistic effect, suggesting that targeting the TRAF6 could be a beneficial co-strategy for managing alloimmune responses. Importantly, our results position TRAF6 as a promising complementary target for enhancing outcomes in CAV.